Titanium lag screw osteosynthesis in the management of mandibular fractures - Haranal, Shashidevi R; Neeli, Arati S; Suryavanshi, R K; Kotrashetti, S M; Naresh, Nitesh (International Multidisciplinary Research Journal, 2012)
Aims and objectives: To evaluate the efficiency of titanium lag screws in the management of oblique and sagittally displaced mandibular fractures. Also to analyze various complications encountered through this technique. Materials and methods: Twenty cases presenting with mandibular oblique, sagittaly displaced mandibular fractures requiring were selected in our study. Titanium lag screws were placed such that their axes bisect the angle between a perpendicular drawn to the fracture line and perpendicular to the bone surface. Postoperative follow up was done for 3to 9 months Results: Majority of the fractures (10) were parasymphysis fractures, 3 with associated fractures. Intermaxillary fixation was used in two of these cases as the fracture fragments were severely displaced (Table1). In two patients, a single lag screw combined with a small conventional miniplate and a bone graft was used, due to loss of bone along the inferior border of the mandible in the fractured site. Two lag screws were used in severely displaced symphysis fractures and when two fracture sites were seen. Adequate rigidity and stability of fractured segments was achieved in all the cases. Conclusion : Titanium lag screw fixation was found to have good rigidity, stability, economic and less time consuming in certain type of mandibular fractures, though there exists few contraindications regarding its usage. It is definitely a technique sensitive procedure, requiring strict adherence to the principle if lag screw placement and adequate knowledge about internal anatomy of the mandible.